2000
DOI: 10.1055/s-2000-9908
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Coumarin Derivatives from the Fern Cyclosorus interruptus

Abstract: Three new coumarin derivatives, compounds 1-3, three new furanocoumarins, compounds 4-6, and a novel dioxocane derivative, compound 7, were isolated from the fern Cyclosorus interruptus (Willd.) H. Itô. Based on spectrometric and spectroscopic analysis (FAB or El mass spectrometry as well as 1D and 2D NMR experiments) their structures were characterised as 5,7-dihydroxy-6-methyl-4-phenyl-8-(3-phenylpropionyl)-1-benzopyran-2-one (1), 5,7-dihydroxy-6-methyl-4-phenyl-8-(3-phenyl-trans-acryloyl)-1- benzopyran-2-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…The screen for activity against the KB cell line (ATC CCL 17) was performed as described previously [9].…”
Section: Experimental Partmentioning
confidence: 99%
“…The screen for activity against the KB cell line (ATC CCL 17) was performed as described previously [9].…”
Section: Experimental Partmentioning
confidence: 99%
“…It has been reported that flavonoids from Saussurea species display a wide range of pharmacological activities, such as anti-inflammatory (Nie et al, 2000), antineoplastic (Huang and Tan, 2002) and anti-oxidant activities (Fan and Yue, 2003). Coumarins are best known to have anticancer and antiviral (Ju et al, 2002), antiplatelet aggregation and antibacterial activities (Quadri-Spinelli et al, 2000). Phenylpropanoids also have antiallergic activity (Matsuda et al, 2003a,b), antimicrobial activity (Shadle et al, 2003), cancer chemopreventive activity (Itoigawa et al, 2004) and gastroprotective effects (Matsuda et al, 2003a,b).…”
Section: Introductionmentioning
confidence: 98%
“…1 Since ancient times there has been strong interest in the application of ferns for their traditional medicinal properties [2][3][4] and in Central American countries ferns are traded in the local markets for medicinal uses. 5 While the chemical composition of primary and secondary metabolites in ferns have been examined, [6][7][8] few reports have characterized the volatile components from aromatic ferns. 9 The genus Anemia Sw. (Anemiaceae) contains over 100 species of aromatic ferns that are utilized in popular medicine, 10 with the great majority found in the warmer and drier regions of America from Texas to Argentina.…”
Section: Introductionmentioning
confidence: 99%